Prognostic value of extended cardiac risk assessment before elective open abdominal aortic surgery - Sigl, Martin; Baumann, Stefan; Könemann, Ann-Sophie; Keese, Michael; Schwenke, Kay; Gerken, Andreas; Dürschmied, Daniel; Rosenkaimer, Stephanie L. (Herz, 2023)
Background: Major vascular surgery is associated with a high perioperative risk and significant mortality. Despite advances in risk stratification, monitoring, and management of perioperative complications, cardiac complications are still common. Stress echocardiography is well established in coronary artery disease diagnostics; however, its prognostic value before high-risk aortic surgery is unknown. This prospective, single-center study compared the outcome of patients undergoing extended cardiac risk assessment before open abdominal aortic surgery with the outcome of patients who had received standard preoperative assessment. Methods: The study included patients undergoing elective open abdominal aortic surgery. Patients who underwent standard preoperative assessment before the start of a dedicated protocol were compared with patients who had extended cardiac risk assessment, including dobutamine stress echocardiography, as part of a stepwise interdisciplinary cardiovascular team approach. The combined primary endpoint was cardiovascular death, myocardial infarction, emergency coronary revascularization, and life-threatening arrhythmia within 30 days. The secondary endpoint was acute renal failure and severe bleeding.Results: In total, 77 patients (mean age 68.1± 8.1 years, 70% male) were included: 39 underwent standard and 38 underwent cardiac risk assessment. The combined primary endpoint was reached significantly more often in patients before than after implementation of the extended cardiac stratification procedure (15% vs. 0%, p= 0.025). The combined secondary endpoint did not differ between the groups. Conclusions: Patients with extended cardiac risk assessment undergoing elective open abdominal aortic surgery had better 30-day outcomes than did those who had standard preoperative assessment.